2019
DOI: 10.1186/s40545-019-0174-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of disposal practices of expired and unused medications among community pharmacies in Anambra State southeast Nigeria: a mixed study design

Abstract: Background Expired or unused medicines are potentially toxic substances that should be managed effectively to avoid accumulation of potentially toxic pharmaceuticals in the environment. In Nigeria, there is currently limited literature on the methods and protocols used by community pharmacists in the disposal of expired drugs. This study assessed disposal practices of expired and unused medications by pharmacists in Anambra State and compared them to the National Agency for Food and Drug Administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 44 publications
7
48
2
6
Order By: Relevance
“…This made some respondents to respectively considered accidental ingestion of leftover and expired medicines, land and water pollution and drugs toxicity, though there was a signi cant difference between LDS and HDS (p = 0001). The reported consequences were in agreement with previous studies in Nigeria [24,56] and Ethiopia [27] and Malaysia [54], and in systematic reviews [52]. There were trace concentrations of medicine APIs in conventional drinking water resources and land lls leachates [58].…”
Section: Perceived Consequences Of Indiscriminate Disposal Of Unused supporting
confidence: 90%
“…This made some respondents to respectively considered accidental ingestion of leftover and expired medicines, land and water pollution and drugs toxicity, though there was a signi cant difference between LDS and HDS (p = 0001). The reported consequences were in agreement with previous studies in Nigeria [24,56] and Ethiopia [27] and Malaysia [54], and in systematic reviews [52]. There were trace concentrations of medicine APIs in conventional drinking water resources and land lls leachates [58].…”
Section: Perceived Consequences Of Indiscriminate Disposal Of Unused supporting
confidence: 90%
“…2,[5][6][7] Improper medication disposal is a worldwide problem that leads to health problems such as ineffective therapy, drug resistance, medication non-adherence, hospitalization, and an overall increase in health-care costs. 4,8,9 Although different studies have been conducted in developed countries to determine the extent of improper medicine disposal, the problem is not well documented in developing countries, and hence a knowledge gap exists regarding the disposal of unused medications among patients in developing countries. 4 Studies conducted in different countries indicated there were diverse practices of disposal of unused medicine.…”
Section: Introductionmentioning
confidence: 99%
“…(Oliveira, et al, 2015) estudou a implantação de postos de coletas de medicamentos em Unidades Básicas de Saúde e coletou-se 23,7 kg de material sendo que medicamentos foram responsáveis por 38,5% deste total. (Michael, et al, 2019) trouxe como dado novo um dado em seu estudo, 31,8% da população estudada descartava os medicamentos através da Agência Nacional de Administração e Controle de Alimentos e Medicamentos. (Ramos, et al, 2017) notou que o descarte adequado esteve fortemente associado a fatores como a maior escolaridade, maior classificação econômica, sexo masculino e ao fato de ter recebido informação sobre o tema.…”
Section: Resultsunclassified